Pergeseran Kaidah Bahasa Indonesia di Kalangan Gen Z dan Milenial Akibat Dampak Teknologi dan Budaya Pop - Gloria Wiryajaya; Salsabila Shafa Rosadi; Yulianti Sarumaha; Zahrina Afifah Saragih; Elda Santoso; Rosmaini Rosmaini (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Indonesian as the national language and official language of the country plays an important role in people's lives, especially in the field of education. However, along with developments in technology and pop culture, the use of Indonesian among generation Z and millennials has experienced significant changes. Generation Z (born 1996–2012) and the millennial generation (born 1980–2000) are more likely to adopt foreign languages ​​and practice code-switching or code-mixing, which influences the rules for good and correct use of Indonesian. Digital technology, especially social media, as well as global pop culture, such as the Korean Wave, have accelerated this shift in language rules. This research aims to identify factors that influence the shift in Indonesian language rules among Gen Z and millennials. Using a literature review method, this research analyzes literature that discusses the phenomenon of language use by the younger generation. The research results show that social media, social media, prestige, advertising and pop culture trends are the main factors that trigger shifts in language rules. This research provides insight into how technological developments and pop culture play a role in language change, as well as providing suggestions for maintaining the continuity of Indonesian language rules.